Upaya Meningkatkan Kolaborasi Peserta Didik SMAN 2 Kediri Melalui Model Pembelajaran ASICC - Wulandari, Hesti Mei; Putri, Prianka Delvina; Utami, Budhi; Primandiri, Poppy Rahmatika (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Collaboration is a crucial learning skill that enables students to solve problems collectively and gain practical experience relevant to everyday life. Based on observations, researchers found that many students prefer to work independently and have an average of 58% in the low category. Therefore, it is necessary to conduct classroom action research (CAR) based on lesson study. This study aims to improve students' collaboration skills through the implementation of the ASICC learning model based on lesson study. This type of research is classroom action research conducted in two cycles. Data on students' collaboration skills were summarized as percentages in each cycle and meeting, and then compared to assess the increase in collaboration from the pre-cycle to cycle 1 and cycle 2. The study's results revealed an increase from 74.8% in cycle 1 to 85.1% in cycle 2. Thus, the implementation of the ASICC learning model is effective in improving student collaboration scores at SMAN 2 Kediri. Kata kunci: pembelajaran, ASICC, kolaborasi